Pengembangan Sistem Monitoring Tingkat Stres berbasis Website - Diva Fardiana Risa; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Stress is the initial stage of the sequence of mental disorders such as depression, and others. Stress has a huge impact on the health of sufferers, but there are still many people who underestimate the existence of this stressful disease. The age of someone who is susceptible to stress is a teenager who is taking high school level education because adolescence is the age of a person to start thinking complex. One solution that has been provided to reduce the impact of stress is facilitating the counselling teacher for high school students. However, most students still feel reluctant to conduct guidance because of erratic schedules and feel ashamed. The development of Website-Based Stress Level Monitoring System aims to simplify the process of stress monitoring and consultation of students and counselling teachers. This system will be used by the counselling teacher, homeroom teacher and admin also by the Students. The Waterfall method is used in the process of developing this system by referring to 35 functional requirements and one non-functional requirement. Furthermore, the system is implemented in several programming languages ​​such as HTML, CSS, Javascript, PHP by using Laravel as a framework. In addition, this system also uses the API from Twitter and the Naive Bayes method library to help the process of capturing the status of students' tweets to conduct a stress level detection process which will be divided into 3 levels: low, medium and high. This system testing is carried out using the white box method for unit testing and integration and black box for conducting validation testing. This test resulted in 100% valid in 85 test cases. Non-functional requirements of the system have been tested by the Sortsite tool, indicating that this website can be operated on several search engines.